Entrepreneurship Orientation and Business Performance: Do Business Strategy and Government Policy Matter? - Aisyah, Esy Nur; Prajawati, Maretha Ika; Yuliati, Yuliati (School of Business, IPB University (SB-IPB), 2025)
Background: Entrepreneurial-oriented business actors are better able to innovate and create products or services that align with market needs. It helps them stay relevant and competitive. Entrepreneurial orientation is closely related to the competitiveness of companies and the acquisition of competitive advantages. Thus, entrepreneurial orientation is critical to the sustainability of MSMEs and contributes to overall economic growth.Purpose: This research investigates the influence of entrepreneurial organizations on the performance of halal food-based Micro, Small, and Medium Enterprises (MSMEs) in developing countries. This study further explains business strategy as a mediating role and government policy as a moderator in the relationship between entrepreneurial orientation and business performance. Design/methodology/approach: This research uses hierarchical regression techniques using cross-sectional data collected from March to April 2024 from 180 MSMEs based on the halal food sector in Malang City, Indonesia. This study relies on resource-based theory, which provides a theoretical lens to test the hypothesized relationships between EO, business strategy, government policy, and halal food business performance. Findings/Result: The findings show that business strategy and government policy are essential in the relationship between entrepreneurial organizations and business performance. Namely, EOs of halal food businesses can improve business performance both directly and indirectly through their business strategies. Government policies can also increase EO's influence on their business performance. Conclusion: This study has practical implications for management and policymakers. Regarding its practical implications for management, research shows that government policies strengthen the influence of EO on business performance. Therefore, halal food entrepreneurs can take advantage of the institutional environment, such as government policies, programs and norms, and societal norms, to develop and strategically improve their business performance.Originality/value (State of the art): This study emphasizes the importance of long-term growth over short-term profits for MSMEs. The capacity for long-term development is considered necessary for MSMEs, and this study reveals the impact of entrepreneurial orientation on MSME growth and performance both directly and through business strategies with strengthening from government support. Keywords: entrepreneurial orientation, business performance, business strategy, government policy